Poland : The Path to a Market Economy - Christofides, Charalambos (Occasional Papers; Occasional Paper ;, 1994)
Poland's economy rebounded dramatically in 1992-93, several years after the nation embarded on a comprehensive program of economic transformation. This paper describes Polan's steps in the areas of public finance, monetary policy and financial sector reform, trade and exchange rate policy, and microeconomic liberalization, as well as the social impact of transition.